Analisis Potensi Olahraga Pariwisata Di Kabupaten Mandailing Natal - Fadhlan Azhari Lubis; Anton Komaini; Endang Sepdanius (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
Problems in this study, From the observations of researchers in several sub-districts, it was found that several tourist attractions had not been implemented properly, management management had not been implemented, access to tourist sites was still inadequate and infrastructure facilities were still lacking. Based on the description above and seeing that there is no tourism sport that has developed there, it is necessary to analyze and identify what tourism sports potential can be developed and can be expected to assist in the development of the tourism sports sector. This type of research is a qualitative research with a descriptive approach. When the research was conducted in May-June before the researchers had made a first visit, and the place of research. Data collection techniques with interviews, observations and documentation of data analysis techniques use techniques using the Miles and Huberman model, namely data reduction, data display, conclusion drawing/verification, and data triangulation. Based on the results of the research above, it can be concluded that it has the potential for tourism sports that can be developed, namely white water rafting located in Tambangan District and motocross sports located in Panyabungan City District. Both of these sports can be developed because in terms of access to the location, it can be said to be good and in terms of infrastructure for rafting sports, it is quite adequate, but in motocross sports, the infrastructure is not sufficient, if equipped, this motocross sport is very good for sports. developed.